Veil (Niqâb) Problematics in Islamic Law Perspective; Religion or Culture? (Islamic Legal Approach) - Mohammad Yusuf Setyawan; Owusu-Ansah David (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2021)
The phenomenon of wearing veil (niqâb) by Muslim women in Indonesia leads to negative perspectives frequently by the majority. Recently, mass media has also highlighted polemics related to the prohibition of wearing the veil in certain institutions and events repeatedly. This study aims to reveal the position of wearing niqab in the perspective of Islamic law, whether it is a part of religious dogma that must be maintained, or is it just a certain community’s culture that is not an obligation for every Muslim. A legal approach in Islamic studies related to the veil phenomenon is needed to reveal the status of wearing a veil. This kind of research is library research using descriptive qualitative research methods. From this study, it was found that the majority of Islamic jurists and sharia experts decided that a woman's face was not included in the genitals. Their decisions rely on Quran and sunnah as the main sources of Islamic law. The scholars are not really questioning the habituation of wearing the veil in Arab society because it was already being a fashion culture of some people there. In order to wear a veil is included in the category of mubah, is not something that is ordered or even prohibited by religion. If a woman's face is not genitals, then under certain conditions, especially when she got pressure, she is expected to show her face. Research related to the law of wearing a veil with other approaches such as theology, phenomenology, culture, etc. will be very helpful in solving the problem of wearing the veil in Indonesia.